Prevalence and Risk Factors Associated with Prehypertension by Gender and Age in a Korean Population in the KNHANES 2010-2012 - Youngbum KIM; Seunghee LEE (Tehran University of Medical Sciences, 2015)
Background: Prehypertension frequently progresses into hypertension and is related to an increased risk of cardiovascular disease. We studied the prevalence of prehypertension and their determinants by gender and age. Methods: The study used nationally representative data from 11,754 participants aged 20-91 years collected between 2010-2012 Korea National Health and Nutrition Examination Surveys (KNHANES). Results: Prehypertension was more prevalent in men than women (aOR = 2.48, CI = 2.11-2.92). Aging was positively associated with prehypertension (40-59 vs. 20-39, aOR = 1.79, CI = 1.55-2.05; 60+ vs. 20-39, aOR = 2.89, CI = 2.35-3.56). In women aged ≥60, prehypertension was associated with WC (aOR = 1.04, CI = 1.00-1.07), whereas in both men and women aged 20-39, it was associated with BMI (men, aOR = 1.14, CI = 1.04-1.24; women, aOR = 1.08, CI = 1.01-1.16). In subjects aged 40-59, age (men, aOR = 1.03, CI = 1.01-1.06; women, aOR = 1.05, CI = 1.02-1.07) was the significant factor increasing the risk of prehypertension, whereas smoking (men, aOR = 0.55, CI = 0.38-0.80; women, aOR = 0.43, CI = 0.24-0.76) showed an inverse association with prehypertension. Alcohol intake showed a positive association with prehypertension in only men aged 40-59. Conclusion: Our findings suggest that different gender/age groups may have different patterns of risk factors associated with prehypertension. Thus, healthcare providers should consider both gender and age when designing community-based interventions for controlling BP and reducing prehypertension.   Keywords: Prehypertension, Risk factor, Gender, Age, Korea